The wars of America - Leckie, Robert (Harper Collins, 1992)
The Wars of America is a dramatic and compelling narrative history by an outstanding military historian of America's armed conflicts and the political, cultural and economic factors behind them since the earliest explorers and settlers arrived on this continent. First published in 1968, It was revised and updated in 1981 to include the Vietnam War. It has now been updated to include all the events of the last ten years in Lebanon, Grenada, Panama, and the victory over Iraq in the Persian Gulf by United Nations forces under the command of General Norman Schwarzkopf. A final chapter analyzes the self-destruction of the European communist world in the summer and fall of 1991, including the collapse of the hard-line Soviet government and the upheavals in Yugoslavia, and speculates on the meaning of these developments on America's future. Leckie not only stresses those personal aspects of war that make it the most intense and contradictory of our experiences. In the new chapters he shows how, while operating in a quintessentially American tradition, our military and political leaders applied the tragic lessons learned in the war in Southeast Asia against North Vietnam by changing from a conscripted to a volunteer army, thus leading the way to better training methods, higher morale, and far better performance on the battlefield. Combining dramatic narrative with sound reference material, The Wars of America is essential for anyone who wishes to understand America at war.
Keywords: Geschichte; Krieg; USA; United States -- History, Military